Bis(Acesulfamato-κ2N3,O4)bis(2-Aminopyrimidine-κN1)copper(II) - Bulut, A.; Íçbudak, H.; Sezer, G.; Kazak, C. (Blackwell Munksgaard, 2005)
In the crystal structure of the title compound, bis(2-amino-pyrimidine- κN1)bis[6-methyl-1,2,3-oxathiazin-4(3H)-one 2,2-dioxide(1-)-κ2N3,O4]copper(II), [Cu(C4H4NO4S)2(C4H 5N3)2], the first mixed-ligand complex of acesulfame, the CuII centre resides on a centre of symmetry and has an octahedral geometry that is distorted both by the presence of four-membered chelate rings and by the Jahn-Teller effect. The equatorial plane is formed by the N atoms of two amino-pyrimidine (ampym) ligands and by the weakly basic carbonyl O atoms of the acesulfamate ligands, while the more basic deprotonated N atoms of these ligands are in the elongated axial positions with a strong misdirected valence. The crystal is stabilized by pyrimidine ring stacking and by intermolecular hydrogen bonding involving the NH2 moiety of the ampym ligand and the carbonyl O atom of the acesulfamate moiety. © 2005 International Union of Crystallography.